Improvement in Health-Related Quality of Life After Community Acquired Pediatric Septic Shock - Pinto, Neethi P.; Berg, Robert A.; Zuppa, Athena F.; Newth, Christopher J.; Pollack, Murray M.; Meert, Kathleen L.; Hall, Mark W.; Quasney, Michael; Sapru, Anil; Carcillo, Joseph A.; McQuillen, Patrick S.; Mourani, Peter M.; et al. (Frontiers in Pediatrics, 2021)
Background: Although some pediatric sepsis survivors experience worsening health-related quality of life (HRQL), many return to their pre-illness HRQL. Whether children can improve beyond baseline is not known. We examined a cohort of pediatric sepsis survivors to determine if those with baseline HRQL scores below the population mean could exhibit >=10% improvement and evaluated factors associated with improvement. Methods: In this secondary analysis of the Life After Pediatric Sepsis Evaluation prospective study, children aged 1 month to 18 years admitted to 12 academic PICUs in the United States with community-acquired septic shock who survived to 3 months and had baseline HRQL scores ≤ 80 (i.e., excluding those with good baseline HRQL to allow for potential improvement) were included. HRQL was measured using the Pediatric Quality of Life Inventory or Stein-Jessop Functional Status Scale. Findings: 117 children were eligible. Sixty-one (52%) had>= 10% improvement in HRQL by 3 months. Lower pre-sepsis HRQL was associated with increased odds of improvement at 3 months (aOR=1.08, 95% CI (1.04-1.11), p<.001) and 12 months (aOR=1.05, 95% CI (1.02-1.11), p=0.005). Improvement in HRQL was most prevalent at 3 month follow-up; at 12 month follow-up, improvement was more sustained among children without severe developmental delay compared to children with severe developmental delay. Interpretation: More than half of these children with community acquired septic shock experienced at least a 10% improvement in HRQL from baseline to 3 months. Children with severe developmental delay did not sustain this improvement at 12 month follow-up.